Local and global Semantic Networks for the representation of music information - Adriano Baratè; Luca Andrea Ludovico (Je-LKS: Journal of E-Learning and Knowledge Society, 2016)
In the field of music informatics, multilayer representation formats are becoming increasingly important, since they enable an integrated and synchronized representation of the various entities that describe a piece of music, from the digital encoding of score symbols to its typographic aspects and audio recordings. Often these formats are based on the eXtensible Markup Language (XML), that allows information embedding, hierarchical structuring and interconnection within a single document. Simultaneously, the advent of the so-called Semantic Web is leading to the transformation of the World Wide Web into an environment where documents are associated with data and metadata. XML is extensively used also in the Semantic Web, since this format supports not only human- but also machine-readable tags. On the one side the Semantic Web aims to create a set of automatically-detectable relationships among data, thus providing users with a number of non-trivial paths to navigate information in a geographically distributed framework; on the other side, multilayer formats typically operate in a similar way, but at a “local” level. The goal of the present work is to discuss the possibilities emerging from a combined approach, namely by adopting multilayer formats in the Semantic Web, addressing in particular augmented-reality applications. An XML-based international standard known as IEEE 1599 will be employed to show a number of innovative applications in music.